Nanomaterials and Supramolecular Structures Physics, Chemistry, and Applications - Shpak, Anatoliy Petrovych; Gorbyk, Petr Petrovych (Springer Netherlands : Imprint: Springer, 2010)
The text features experimental investigations which use a variety of modern methods and theoretical modeling of surface structures and physicochemical processes which occur at solid surfaces. Nanomaterials and Supramolecular Structures: Physics, Chemistry, and Applications is intended for specialists experienced in the fields of Nanochemistry, Nanophysics, Surface Chemistry (and Physics), synthesis of new nanostructural functional materials and their practical applications. It will also prove useful to students, post-graduates, researchers, and lecturers.